PENDAMPINGAN POKDARWIS DESA WISATA PERANCAK DALAM MENENTUKAN TARGET PASAR PARIWISATA - I.M. Adikampana; I.N. Sunarta; L.P.K. Pujani; P.K. Sanjiwani (Buletin Udayana Mengabdi, 2021)
Perancak Tourist Village is located in Jembrana, West Bali. This destination has a natural and spiritual uniqueness that has been developed as a marine-based tourism attraction. However, the existence of these tourist attractions has not obtained a significant response from tourists or the tourism market. This issue is caused by the limitations of Pokdarwis as the management or hereinafter referred to as the counterpart in determining the appropriate tourism target market. Based on the situation, an assistant program for Pokdarwis is urgently involved to identify the target market of the Perancak Tourist Village. Assistance is carried out by conducting a market analysis workshop. The existence of the assistant program has enabled the community to directly determine the tourism market or target tourists who are interested in visiting this rural tourism destination on the west side of the island of Bali.Keywords: assistant program, Pokdarwis, market target, Perancak tourist village